DEVELOPMENT AND COMPARATIVE ASSESSMENT OF REGENERATED LINES OF CUCUMBER - I. V. Vardanyan; L. M. Tadevosyan; V. A. Meloyan; Z. E. Arutyunyan (Овощи России)
Application of such biotechnological method as a callus culture, allowed developing the somaclonal variants of cucumber, six of which were selected as a regenerated lines for the breeding program. New forms are characterized by early-ripeness, percent of parthenocarpy, good quality, yield and fruit weight. These lines can be used as an initial material for heterosis breeding and for improvement of donor cultivars of cucumber.